Perceptual and motor responses directly and indirectly mediate the effects of noxious stimuli on autonomic responses. Issue 12 (December 2019) - Tiemann, Laura; Hohn, Vanessa D.; Ta Dinh, Son; May, Elisabeth S.; Nickel, Moritz M.; Heitmann, Henrik; Ploner, Markus
Abstract : Abstract: Autonomic responses are an essential component of pain. They serve its adaptive function by regulating homeostasis and providing resources for protective and recuperative responses to noxious stimuli. To be adaptive and flexible, autonomic responses are not only determined by noxious stimulus characteristics, but likely also shaped by perceptual and motor responses to noxious stimuli. However, it is not fully known how noxious stimulus characteristics, perceptual responses, and motor responses interact in shaping autonomic responses. To address this question, we collected perceptual, motor, and autonomic responses to brief noxious laser stimuli of different intensities in 47 healthy human participants. Multilevel 2-path mediation analyses revealed that perceptual, but not motor responses mediated the translation of noxious stimuli into autonomic responses. Multilevel 3-path mediation analyses further specified that motor responses indirectly related to autonomic responses through their close association with perceptual responses. These findings confirm that autonomic responses are not only a reflexive reaction to noxious stimuli, but directly and indirectly shaped by perceptual and motor responses, respectively. These effects of motor and perceptual processes on autonomic responses likely allow for the integration of contextual processes into protective and regulatory autonomic responses, aiding adaptive and flexible coping with threat. Abstract : Motor and perceptual processes shape autonomic responses to noxious stimuli, which likely serves the integration of contextual processes into flexible and adaptive responses to threat.